Influence of flame retardants on the mechanism of pyrolysis of cotton (cellulose) fabrics in air - (:unkn) unknown (ELSEVIER SCIENCE BV, 1997)
A revised model for the influence of flame retardant treatments on the pyrolysis behaviour, in air, of cotton (cellulose) fabrics is proposed. This is based on extensive studies of a set of commercially flame retarded cotton fabrics using a range of experimental techniques, e.g., Py-FTIR, Py/GC and CC-MS, thermal analysis, oxygen index/smoke-CO-CO2 evolution. The samples studied were the condensed phase active ammonium polyphosphate (Amgard TR), a phosphonium salt-urea-polycondensate (Proban CC) from Albright and Wilson and a phosphonopropionamide (Pyrovatex CP) from Ciba-Geigy, together with two vapour phase active treatments: ammonium phosphate-ammonium bromide (Amguard CD, Albright and Wilson) and an antimony(III) oxide-aliphatic bromide (Flacavon H14/587) formulation from Schill and Seilacher. The results obtained are collated and interpreted to provide an overall view of the pyrolysis mechanism of cellulose in air. The pyrolysis can be characterised by three stages: Stage I, 300-400 degrees C, involves two competing pathways which yield aliphatic char and volatiles. During Stage II, 400-800 degrees C, some of the aliphatic char converts to an aromatic form. Both chars are partially oxidised to evolve CO and CO2. Above 800 degrees C, Stage III, char and any remaining hydrocarbon species are further oxidised mainly to CO2 and some CO. The influence of the various flame retardant types on these various Stages are discussed with respect to their retardant roles. (C) 1997 Elsevier Science B.V.
Keywords: cotton fabrics; cellulose; pyrolysis; mechanism; flame retardants; SINGLE LAYER FABRICS; CO EVOLUTION; INVESTIGATE; BEHAVIOR; SMOKE; GAS